Development of learning module to improve competency achievement in the department of civil engineering education in Indonesia - Daryono, Rihab Wit; Rochmadi, Sunar (Research and Social Study Institute, 2020)
The purpose of this study was to determine the process of preparation and feasibility of the Building Maintenance learning module in the Department of Civil Engineering in vocational high schools. This research is a research and development (R&D) study using the Four D (4D) model. The Building Maintenance learning module is validated by one material expert and one media expert and the Building Maintenance subject teacher. The module contains a title, introduction, learning, evaluation questions, UAS, answer key, and bibliography. The analysis shows that the learning module as a whole is very feasible to be used as a teaching material. The results of the analysis of the data obtained an average score from the material experts isÂ 90.0% so that it belongs to the